Atuação no PELC-Povos e comunidades tradicionais da UFSM: relações com a formação inicial em educação física - Castilhos, Rosane Lorentz (2017)
The present master’s dissertation had as subjects matter the Sport and Leisure Program of City – Traditional People and Communities – Quilombolas and Rural of University Federal of Santa Maria (SLPC/TPC/UFSM) and initial education of teacher of Physical Education and Sport Centre (UESC) of institution concerned. The research aimed to understand how acting experience as social agents at SLPC/PCT/UFSM reverberated in initial education of Physical Education academics of UESC/UFSM. The justification has emerged of questions observed as integrant of Program management team, against intricacies faced by academics that yet in training process, would recruit study periods and meeting between themselves and with project coordination, in perspective to heal difficulties, to look for knowledge and consequently to qualify actions as social agents in communities involved. Methodological ways has characterized by a qualitative research as study of case, using semi-structured interviews as instrument for getting of searches sources with five participating academics of study and content analysis method (Franco, 2012) to analyse them. Through of this method, we found five categories: the choice of Physical Education course; initial education at Physical Education course of PEDC/FUSM; Quilombolas and rural communities; regent activities of social agents’ routine of SLPC/TPC and action legacies at SLPC/TPC/FUSM front initial education in Physical Education of PESC/FUSM. This way for concluding, even in the light of the points, which exhibited different ways of repercussion front initial education at PE of these academics, the view besides academic world is necessary. Because even these points has been relevant contributions for initial education, the inserts in SLP/TPC/FUSM also corroborate with learnings about to live in community, respect to diversity, overcoming adversity and to provide to these people that understanding their rights of citizens.